Metal bioaccumulation and genotoxicity in Oreochromis niloticus reared in farming pools influenced by mining activities in Napo, in the Ecuadorian Amazonia - Vasco Viteri, Samantha (2023)
Mining areas may suffer long-term metal contamination and represent harmful remnants of former mining ac tivities. In the northern Amazon of Ecuador, former mining waste pits are used in Oreochromis niloticus (Nile tilapia) fish farming. Given the high consumption of this species by the local population, we aimed to estimate human consumption risks by determining Cd, Cu, Cr, Pb, and Zn tissue bioaccumulation (liver, gills, and muscle) and genotoxicity (micronucleus essay) in tilapia cultivated in one former mining waste pit (S3) and compare the findings to tilapias reared in two non-mining areas (S1 and S2); 15 fish total. Tissue metal content was not significantly higher in S3 than in non-mining areas. Cu and Cd were higher in the gills of tilapias from S1 compared to the other study sites. Higher Cd and Zn were detected in the liver of tilapias from S1 compared to the other sampling sites. Cu was higher in the liver of fish from S1 and S2, and Cr, in the gills of fish from S1. The highest frequency of nuclear abnormalities was observed in fish from S3, indicating chronic exposure to metals a